The implementation of Responsibility to Protect (R2P) in conflict zones - Mohd Hedzir Omar,; Noraini Zulkifli, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Responsibility to Protect (R2P) emerged as a standard in response to the crime of mass atrocities and human rights violations in the 1990s. R2P is implemented in response to severe human rights crises such as those in Bosnia and Rwanda. The R2P principle aimed to replace the so-called current and somewhat contentious notion of humanitarian intervention and provide states with legal grounds for military action to safeguard human rights in countries where the government threatens these same freedoms. This new approach is based not only on crisis response but also on measures to avoid circumstances that make the commission of mass atrocity crimes easier and ultimate. This study has three objectives: 1) to understand R2P, 2) to examine the implementation of R2P in Conflict Zones, and 3) to analyse the legal basis of R2P. The research found that (1) the R2P is a physical manifestation of the international community’s determination to uphold its responsibility to protect men, women and children at risk of genocide, ethnic cleansing, war crimes and crimes against humanity, (2) theoretically, R2P is a legitimate measure in ensuring the protection of the population, particularly those who are vulnerable, and (3) R2P is not bound by any relevant legal aspect, thus making its effectual implementation not as effective as it should be.